"TOGETHER WE ARE UNBEATABLE": young sisters' narration of a sibling's cancer in personal blogs on the internet. Issue 1 (1st January 2019) - Silvén Hagström, Anneli; Toft, Teolinda
ABSTRACT: Purpose : Siblings of children and young people diagnosed with cancer are commonly reluctant to talk about their experiences due to the circumstances of the illness situation. This article aims to bring voice to experience and inform practice by investigating what and how three young sisters narrate about their illness experiences in personal blogs on the Internet. Methods : A narrative methodology for the analysis of life storytelling was applied primarily to investigate the sister's coping strategies and support needs. Results : The results show how the sisters constructed their own space for narration, with the main aims of expressing their feelings about the illness and seeking social support. The telling of their experiences along with encouraging comments from a supportive audience enabled a change in position from feeling neglected and silenced to being a recognized agent and caring sister. In addition, through their narrative coping the sisters went from powerless to powerful in their position in relation to cancer. Conclusion : The results highlight the need for siblings to be able to narrate experience in a supportive context, where the processing of their relationship with the ill sister/brother should be understood as an important element of their coping with cancer and death.